Effect of Strengthening Exercises on Serum C-Reactive Protein After Coronary Artery Bypass Grafts - M Salarifar; K Tavakol; MR Hadian; H Bagheri; B Attarbashi Moghadam; M Nejatian (Tehran University of Medical Sciences, 2008)
Background: Strengthening exercises are not favored in the rehabilitation of patients after coronary artery bypass grafts (CABG) for concerns over potential adverse effects. However, patients often present with weakened skeletal muscles post CABG due to disuse. Methods: We studied the effects of aerobic and strengthening exercises on the serum C-reactive protein (CRP) levels and blood pressure in 79 post CABG patients aged 40-60 years. Patients were randomly assigned to one of four programs five days per week, consisting of either aerobic exercises alone (controls) or combined with strengthening exercises (experimentals) at moderate intensity. The serum CRP levels were quantified at the beginning, 12th and 24th sessions, and at 3-month follow-up. Patients blood pressure was measured before and after each exercise session. Patients were re-evaluated at 3-month follow-up. Results: There was a mild but significant increase in the CRP levels at 12th session in all groups. Patients. systolic blood pressures declined by 2%-7% at 12th and 24th sessions, respectively. There was no significant difference in changes of blood pressure among the groups. Conclusion: The results suggest that the four exercise programs were equally safe in low-risk, post CABG patients. Exercises did not promote a systemic inflammatory response. These beneficial effects were still evident at 3-month follow-up.